Endogenous Retroviruses as Targets for Antitumor Immunity in Renal Cell Cancer and Other Tumors - Cherkasova, Elena; Weisman, Quinn; Childs, Richard W. (Frontiers in Oncology, 2013)
Human endogenous retroviruses (HERVs), remnants of ancient germ-line infections with exogenous retroviruses, are estimated to comprise up to 8% of human genome. Most HERVs have accumulated mutations and deletions that prevent their expression as an infectious virus. Nevertheless, a growing number of HERV genes and proteins have been found to be expressed in different cancers, raising the possibility that HERV-derived antigens might represent excellent targets for tumor immunotherapy. Here, we review data showing HERV-encoded antigens are capable of eliciting humoral and T-cells specific antitumor immunity. We also describe a novel HERV-E that was recently found to be selectively expressed in over 80% of clear cell kidney cancer but not in normal tissues. Remarkably, the restricted expression of HERV-E in kidney tumors was found to occur as a consequence of inactivation of the von Hippel–Lindau tumor suppressor. Importantly, antigens derived from this provirus are immunogenic, stimulating cytotoxic T-cells that kill kidney cancer cells in vitro and in vivo. Taken altogether, these data suggest efforts aimed at boosting human immunity against HERV-derived antigens could be used as a strategy to treat advanced tumors including kidney cancer.